Implementing Evidence Based Intervention to Improve Sexual Health in Female Oncology Patients - Aronowitz, Ivey (My University, 2022)
When a patient receives a cancer diagnosis, the entire body can be affected by treatment including sexual health. This evidence-based quality improvement project was designed to increase the oncology nurses understanding of treatments that affect sexual health and in turn, increase the number of proper referrals being made to the sexual health clinic. A pre-implementation survey was administered to the oncology nursing staff to determine a baseline of knowledge around the different types of therapy and how they affect sexual health. The pre-implementation survey was also used to determine the nurses’ level of knowledge on how to interpret the distress tool and how to make proper referrals to the sexual health clinic. Manual chart audits were performed to determine the number of referrals being made to the sexual health clinic prior to the implementation of the project. The project implementation included eight educational sessions to the oncology nursing staff on how to interpret the distress tool, how the different therapies affect a female oncology patient in regards to sexual health, and how to make proper referrals to the sexual health clinic based on a patients need. The same process was repeated post-implementation. Findings showed that there was a positive correlation with increasing the nurse’s base knowledge of sexual health in female oncology patients and the number of referrals made to the sexual health clinic. The analysis of the pre-implementation surveys and post-implementation surveys revealed that the educational sessions yielded a 35% increase in the nurses understanding of sexual health and how to make proper referrals. The number of referrals made to the sexual health clinic increased from 0 per week to an average of 12.5 per week.
Keywords: oncology, sexual health, cancer, female